Multistatic frequency and polarimetry adaptive autofocus for synthetic aperture radar imaging of a moving target - Rattan, Anmol; Andre, Daniel; Finnis, Mark V. (Institution of Engineering and Technology (IET), 2026)
Synthetic Aperture Radar (SAR) images of moving targets are often displaced and defocused, making reliable localisation and recognition difficult. The problem becomes more pronounced when target behaviour departs from simple motion assumptions and is better described by more complex kinematics, such as six‐degrees‐of‐freedom (6‐DoF) motion. Although many autofocus methods rely on subaperture or full‐aperture formulations, such approaches can become restrictive when motion varies nonlinearly over the aperture and finer compensation is required. Multistatic SAR provides additional receiver diversity and, when combined with frequency and polarimetric diversity, it helps constrain this problem; however, such information is not usually exploited explicitly in pulse‐by‐pulse autofocus. This paper introduces a multistatic, frequency‐ and polarimetry‐adaptive autofocus algorithm (F‐Pol) that extends Localised Threshold Sharpness (LTS) into the joint frequency–polarimetric domain by encouraging agreement across frequency sub‐bands and polarisation channels. Experimental validation using the Cranfield University Ground‐Based SAR system with emulated target motion shows that, across the tested signal‐to‐noise ratio (SNR) range of −5 to 20 dB, F‐Pol gives improved image quality and target motion estimation relative to Intensity‐Squared (ISQ) and LTS. Laboratory and supplementary simulation results indicate that joint frequency and polarimetric diversity enhances multistatic SAR autofocus performance.
Keywords: Networking & Telecommunications; 4006 Communications engineering; inverse synthetic aperture radar (ISAR); motion compensation; motion estimation; multistatic radar; radar imaging; synthetic aperture radar; target tracking